Successful staged surgical management of atresia ani with urethrorectal fistula in a male kitten - Nithida Boonwittaya; Wutti Bunjerdsuwan; Piyathip Choochalermporn (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 2-month-old male British Shorthair cat was referred with suspected atresia ani. Physical examination revealed an imperforate anus and dribbling of faecal discharge through the penis. Radiographic findings, along with a retrograde urethrogram, confirmed the diagnosis of type II atresia ani with a urethrorectal fistula. Surgical anoplasty was performed and the patient recovered well. At 8 months of age, surgical treatment for the congenital urethrorectal fistula was carried out via a single perineal approach, including fistulectomy and castration through the same incision. Postoperative short-term outcomes were excellent, with normal defecation and urination. Relevance and novel information Atresia ani is a rare congenital anomaly, particularly in male cats. Despite advancements in surgical techniques, this case represents the first successful staged surgical management of urethrorectal fistula with type II atresia ani in a male kitten, potentially influencing future surgical approaches for similar congenital anomalies.